Definitions of terms in Telehealth - Rudel, Drago (Informatica Medica Slovenica, 2011)
Executive Agency for Health and Consumers supported European-wide project Telehealth Services Code of Practice for Europe - TeleSCopE aims to develop a comprehensive Code of Practice for Telehealth Services. The first output from the Telescope was a report on definitions, terminology and shared understanding of terms relating to telehealth. It is summarised in this article. In parallel in Slovenia, a working group mandated by the Slovenian Medical Informatics Society Executive Board to prepare a draft document for a national telehealth strategy, has prepared the definitions of three basic terms: telemedicine, telehealth and telecare in the Slovenian language. They submitted the definitions to the Board for Standards in Healthcare at the Ministry of Health to include them into the growing Glossary of Terms in Healthcare. These definitions are also presented in this article.
Keywords: Computer Communication Networks; Databases, Bibliographic; Health Services; Nomenclature; Računalniške mreže; Telemedicina; Telemedicine; Zbirke podatkov bibliografske; Zdravstvene službe